On reification: a reinterpretation of designed and emergent practice - Chris Tompsett; Graham Alsop (Association for Learning Technology, 2003)
This paper is a response to the article: 'Examining the five-stage e-moderating model: designed and emergent practice in the learning technology profession, published in ALT-J 11 (1). Whilst we agree with the concerns of the authors on the problems of commodification and the increasing control of learning technology from a financial or predominantly management perspective, we wish to offer a reinterpretation of the research by taking a stricter analysis of the events described by the authors